2017
DOI: 10.1038/nature21382
|View full text |Cite
|
Sign up to set email alerts
|

The molecular architecture of lamins in somatic cells

Abstract: The nuclear lamina is a fundamental constituent of metazoan nuclei. It is composed mainly of lamins, which are intermediate filament proteins that assemble into a filamentous meshwork, bridging the nuclear envelope and chromatin 1–4. Besides providing structural stability to the nucleus 5,6, the lamina is involved in many nuclear activities, including chromatin organization, transcription and replication 7–10. However, the structural organization of the nuclear lamina is poorly understood. Here, we use cryo-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
412
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(441 citation statements)
references
References 41 publications
26
412
2
1
Order By: Relevance
“…Localizing individual or rare proteins and transient biomolecular complexes in situ using cryoEM is difficult due to the crowded cellular landscape that is visible by cryoEM. Currently, proteins are identified by, e.g., immunolabeling using gold beads, or tagged with proteins that accumulate heavy metals to become electron dense . However, these are not optimal, with generally a poor binding efficiency and difficulties with intracellular delivery of both heavy metals and (immuno)labeling agents .…”
Section: Applications and Future Perspectivesmentioning
confidence: 99%
“…Localizing individual or rare proteins and transient biomolecular complexes in situ using cryoEM is difficult due to the crowded cellular landscape that is visible by cryoEM. Currently, proteins are identified by, e.g., immunolabeling using gold beads, or tagged with proteins that accumulate heavy metals to become electron dense . However, these are not optimal, with generally a poor binding efficiency and difficulties with intracellular delivery of both heavy metals and (immuno)labeling agents .…”
Section: Applications and Future Perspectivesmentioning
confidence: 99%
“…The different lamin subtypes are assembled into structurally similar filaments that form a densely interwoven meshwork apposed to the INM [11,12]. Recent cryo-electron tomography revealed that lamin filaments in cultured cells are unexpectedly thin: they have an ~3.5 nm diameter, and most likely contain two dimers per filament cross-section [13 •• ]. By contrast, cytoplasmic intermediate filaments have a diameter of ~10 nm [14].…”
Section: The Regulatory Framework At the Inner Nuclear Membranementioning
confidence: 99%
“…The diagram illustrates the direct connection of the ONM with the peripheral ER, and the lipid bilayer continuity between the ONM and INM at NPCs. Nuclear lamin filaments [13 •• ] are depicted as a green meshwork underlying the INM. Widely studied INM proteins are shown, with transmembrane segments and folded domains represented by cylinders spanning the lipid bilayer and external to it, respectively.…”
Section: Figurementioning
confidence: 99%
“…They bear an NLS leading to their importation into the nucleoplasm. In the nucleus, lamins A and C are constituents of the nuclear matrix: (i) the lamina where they interact with B‐type lamins, with several nuclear envelope transmembrane partner proteins (NETs) of the INM and with the NPC, and (ii) the internal nuclear meshwork forming a component of the nucleoskeleton (Cau et al., 2014; Gruenbaum & Foisner, 2015; Turgay et al., 2017). This lamin meshwork plays a major role in cell structure by conferring the architecture of the nucleoplasm and maintaining the nuclear shape (Ungricht & Kutay, 2017).…”
Section: Lamins and Laminopathiesmentioning
confidence: 99%